The Engineering for Production of a Recording Current Meter - Hodges, G. F. (The International Hydrographic Review, 2015)
This paper describes a recording current meter which makes *full use of a novel electro-mechanical analogue to digital converter to achieve the transfer of information onto standard domestic magnetic tape. To measure the current flow the original meter was designed with a Savonius type rotor but the subsequent user requirement was for a propeller type rotor. This paper describes the further development and engineering carried out to adapt the meter to use a sensitive propeller rotor. The author deals in greater detail with the subsequent engineering work on the instrument as he has been more directly connected with this aspect of the work. Reference is also made to the tape translation unit designed to convert the recorded inform at ion from the magnetic to punched paper tape for final computer infeed.